(NrUSSKIJ U^ENYJ (B- (NmETALLOWED n(B.(Nw(B. (NkALAKUCKIJ (B/s - (N~ERNQK(B, (Na(B.(Nqs; (NnAHIMOW(B, (Nd(B.(Nms ((NmOSKWA (B:s (NmA[GIZ(B,s, 1951)
(NzAKL(B.: (NS(B. 135-137s
(NpODSTR(B. (NPRIME^(B.s
(NlIT(B.: (NS(B. 140-146s
Keywords: (NkALAKUCKIJ(B, (Nn(B.(Nw(B.s; (NwELIKIJ RUSSKIJ U^ENYJs